Performance Generating Systems in Dance Dramaturgy, Psychology, and Performativity - Hansen, Pil (Intellect, 2022)
Analyzes the self-organizing dramaturgies of dance works that generate performance systematically. Provides effective resources for those who wish to study or realize the potential of performance generating systems in dance within the fields of choreography and dance dramaturgy, dance education, community dance, or dance psychology.